Ileocolic Resection for Crohn Disease: The Influence of Different Surgical Techniques on Perioperative Outcomes, Recurrence Rates, and Endoscopic Surveillance. Issue 2 (14th May 2021) - Click, Benjamin; Merchea, Amit; Colibaseanu, Dorin T; Regueiro, Miguel; Farraye, Francis A; Stocchi, Luca
Abstract: Ileocolic resection (ICR) is the most common surgical procedure in Crohn disease (CD). There are many surgical techniques for performing ICRs and subsequent anastomoses. Recurrence of CD after ICR is common, often clinically silent, and thus requires monitoring including periodic use of endoscopy to detect early active disease. There is emerging evidence that surgical approaches may influence CD recurrence. This review explores the various surgical considerations, the data behind each decision, and how these techniques influence subsequent endoscopic surveillance.